An Overview of the Application of Geographic Information Systems (GIS) in Crisis Management with an Emphasis on Flood Zoning - Heydari, Mohammad; Javad Khosravi, Mohammad; Kianinejad, Mohammad Kazem; Yazdanirostam, Faeze; Sadeghian, Azadeh; ShahiriParsa, Ahmad (IJRDO-Journal of Applied Science, 2018)
Early warning is one of the main causes for disaster risk reduction. This will prevent the loss of life and reduce the negative economic and material consequences of accidents. This case study becomes more important when it comes to the geographic conditions exposed to many natural and severe natural disasters such as floods, storms and earthquakes. In order to mitigate the negative effects of facing such a situation, the need for crisis management is absolutely necessary. One of the strongest tools for optimizing crisis management is GIS geographic information systems. Using the GIS software and the use of hydraulic software such as HEC-RAS, it can be used to determine the flood zoning and, consequently, management measures to reduce the risks, with an appropriate precaution before the occurrence, Simulated.